2000
DOI: 10.1111/j.1532-5415.2000.tb06892.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Effectiveness, and Predictors of Planning the Place of Death Among Older Persons Followed in Community‐Based Long Term Care

Abstract: Among a group of frail older persons living in the community, planning to die in a particular place was common and implemented successfully most of the time. Providing physician care at home may facilitate improved end-of-life care for older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 14 publications
1
53
0
Order By: Relevance
“…Nine studies focused on congruence specifically3, 14, 2732, 34 and nine examined preference as one of many factors associated with place of death 10, 12, 17–19, 33, 35–37. Seven studies were from the U.S.,3, 10, 12, 19, 28, 30, 35 three were from the U.K.,27, 33, 34 and four were from Canada 17, 18, 32, 37. Australia,14 Sweden,36 Taiwan29 and Italy31 each had one study included.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies focused on congruence specifically3, 14, 2732, 34 and nine examined preference as one of many factors associated with place of death 10, 12, 17–19, 33, 35–37. Seven studies were from the U.S.,3, 10, 12, 19, 28, 30, 35 three were from the U.K.,27, 33, 34 and four were from Canada 17, 18, 32, 37. Australia,14 Sweden,36 Taiwan29 and Italy31 each had one study included.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest overall congruence and kappa statistic were reported in a grade A study that prospectively elicited patients' preferences 'if everything were possible,' 23 while the study with the highest congruence and kappa statistic were reported in a grade B retrospective chart review of a physician-led house call programme. 26 Among the higher quality prospective studies, three longitudinal studies which reported the patient's final preference prior to death 6,24,25 yielded higher congruence and kappa statistics Table 2 Examples of tables reporting congruence between preferred and actual places of death than the studies that elicited patients' preferences at one point in time. 18,19,23 One study reported a 70% overall congruence, yet the kappa statistic was only 0.17 due to correction for chance agreement based on the distribution of the preferences and places of death.…”
Section: Methods Of Reporting Congruencementioning
confidence: 95%
“…In a US study, 87.2% of the dying preferred a death at home (cancer patients), 4 so did 74% in a Taiwanese study (cancer patients), 13 93.5% in an Italian study (cancer patients), 14 and 82.5% in another US study. 15 A further study from South Australia, interviewing the general population concerning preferred places of death, showed that 70% wanted to die at home if hypothetically dying of a terminal illness. 16 These findings reaffirm the importance of a familiar surrounding and the continuous presence of family and loved ones for the dying.…”
Section: Relevance Of the Findings And Implicationsmentioning
confidence: 98%